Galante feesten - Verlaine, Paul 1844-1896; Van Nimwegen, Arjaan (Amsterdam Athenaeum - Polak & Van Gennep, 1996)
'Fêtes galante's is a collection of poems by Paul Verlaine published in 1869. It is Verlaines second collection, after the 'Poèmes saturniens' of 1866. This short collection, composed of twenty-two poems in very varied metrical forms, highlights scenes of seduction and amorous banter between characters from the world of Italian commedia dell'arte and an idealized countryside. The Dutch translations by Arjaan van Nimwegen are published alongsides the original French poems.
Paul-Marie Verlaine (1844-1896) was a French poet associated with the Symbolist movement and the Decadent movement. He is considered one of the greatest representatives of the fin de siècle in international and French poetry.
Keywords: 19th Century (1801-1900); Poetry; France